A Characterization of Boundedness of Fractional Maximal Operator with Variable Kernel on Herz-Morrey Spaces (Analysis in Theory and Applications, 2022)
A significant number of studies have been carried out on the generalized Lebesgue spaces $L^{p(x)}$, Sobolev spaces $W^{1,p(x)}$ and Herz spaces. In this paper, we demonstrated a characterization of boundedness of the fractional maximal operator with variable kernel on Herz-Morrey spaces.
Keywords: Variable exponent; herz space; operator theory.